Sales Mobile Application Design in Handphone Store - Nuryadi, Nanang; Sudarsono, Bibit; Asistyasari, Ayuni; Nuryanti, Nuryanti (Journal of Applied Engineering and Technological Science (JAETS), 2022)
In the current era of globalization, technology is advancing rapidly, and computers are one of the technologies which are one of the tools used to make it easier to find problems, of course, it is also supported by hardware, software and brainware. Mobile stores require an information system that supports and provides satisfactory service to buyers. For this reason, the author makes this final project regarding the program for selling cellphones at the cellphone store which currently does not use a computerized system. The system at the cellphone store usually still uses a manual system. Starting from recording sales notes to bookkeeping sales reports that are still recorded in the books. This can allow for errors in recording, ineffectiveness and inefficient calculations in large numbers. And can cause inaccurate reports made. The use of the program is one solution to solving sales problems in the cellphone store. Therefore, with the use of a sales program, it is possible to further assist sales activities in the cellphone store.